Internet incidence on SME's sales: A propensity score matching analysis - Alderete, Maria Veronica (2013)
The purpose of this paper is to determine how much is the bonus or prize to the sales per worker of Internet-using firms compared to not Internet-using firms. The author employs matching techniques based on an Argentinean database. The author first presents a binary logit model, in which the dependent variable is a dichotomous variable equal to 1 if the firm adopted Internet and 0 otherwise, to evaluate the factors that influence a firm?s probability of adopting Internet. A propensity score matching (PSM) model is then used to assess the impact of using Internet on the sales per worker. The author finds statically significant differences in the sales average between firms that are similar in many dimensions such as location, size, and sales market except for the Internet adoption decision. By probing that Internet access improves SME's sales, the author is validating the Public Sector ICT modernization programs for SME. The contribution of this paper consists of using a well known technique as PSM to analyze a recent field of research which is the contribution of Internet adoption to the firm's sales per worker.